Safety and clinical efficacy of toripalimab, a PD-1 mAb, in patients with advanced or recurrent malignancies in a phase I study. (May 2020) - Yang, Jianliang; Dong, Lihou; Yang, Sheng; Han, Xiaohong; Han, Ying; Jiang, Shiyu; Yao, Jiarui; Zhang, Zhishang; Zhang, Shuxiang; Liu, Peng; Qin, Yan; Wu, Hai; et al.
Abstract: Purpose: This is a first-in-human phase I study investigating the safety and efficacy of toripalimab, a humanized monoclonal antibody against the programmed cell death-1 (PD-1) receptor, in Chinese patients with advanced or recurrent malignant tumor refractory to standard treatment. Patients and methods: During dose escalation, patients received a single-dose intravenous infusion of toripalimab for 56 days followed by multidose infusions every two weeks. The planned dosing groups were 1, 3 and 10 mg/kg. During dose expansion, patients received toripalimab every two weeks. Clinical response was evaluated by investigators every 6 weeks. Results: Thirty-three patients were enrolled, including 12 patients with alveolar soft part sarcoma (ASPS), seven with non–small-cell lung cancer and 11 with lymphoma. Patients were heavily pretreated with a median of 3 prior lines of systemic treatments. Toripalimab was well tolerated without dose-limiting toxicity. All patients experienced treatment-related adverse events. Grade 3 and above treatment-related adverse events occurred in six (18.2%) patients. Among 22 solid tumors, the objective response rate (ORR) was 22.7% per RECIST v1.1. The ORR was 90.9% in 11 lymphoma patients per IWG 2007. The median duration of response was 21.5 months. The median progression-free survival was 5.7 months for solid tumors and 8.3 months for lymphomas. The median OS was not reached for all patients and the lymphoma subgroups. The median OS was 34.7 months for patients with ASPS. Conclusion: Toripalimab was well tolerated up to 10 mg/kg Q2W without dose-limiting toxicity and showed promising and durable antitumour activities in patients with ASPS and lymphoma, who were heavily pretreated. Clinical trial information: ClinicalTrials.gov Identifier: NCT02836834. Highlights: First-in-human Phase I study of toripalimab in patients with advanced malignant tumor. Toripalimab was well tolerated up to 10mg/kg Q2W without DLT. 25.0% (3/12) ORR and 91.7% (11/12) DCR in alveolar soft part sarcoma patients. 90.9% (10/11) ORR and 90.9% (10/11) DCR in lymphoma patients. Median DOR 21.5 months for all responding patients.